New perspectives for treatment of systemic lupus erythematosus - Narbutt, Joanna (Dermatology Review/Przegląd Dermatologiczny, 2012)
Systemic lupus erythematosus (SLE) is an autoimmune disease which concerns 40/100 000 Europeans and 200/100 000 Afro Americans. New therapeutic methods, especially glucocorticosteroids and immunosuppressive drugs, have prolonged the lifetime of SLE patients within the last 60 years. Because of the complex clinical picture of SLE, it is currently assumed that therapy should be individualized as well as that the main therapeutic goal is to control disease activity. As the drugs in SLE are administered chronically, the choice of therapy should also take into account drugs’ adverse effects. In everyday practice non-steroid anti-inflammatory drugs, antimalarial agents, glucocorticosteroids, azathioprine and cyclophosphamide are most frequently used. Dynamic development of biotechnology and the pharmaceutical industry results in the creation of new biological drugs which might be used in therapy of SLE. In pathogenesis of SLE, B lymphocytes play the key role; thus novel therapy of the disease should, among others, modify activity of these cells. Currently, various monoclonal antibodies are under clinical trials, including proteins against CD20 (rituximab, ofatumumab, ocrelizumab, veltuzumab), against CD22 (epratuzumab), protein blocking BAFF (B-cell lymphocyte-activating factor) and ligand APRIL (atacicept). So far only one molecule – belimumab, blocking BAFF receptor – has been registered for SLE therapy. In the article current knowledge on perspectives for SLE treatment is presented.